2005
DOI: 10.1139/h05-152
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Parameters of the Relationship Between Power and Time to Exhaustion From a Single Ramp Test

Abstract: This study aimed to estimate the power/time relationship from a single ramp test (RT) assuming critical power (Pc) from ventilatory threshold (VT) and energy reserve (W') from total work during RT These estimates from single RT were compared to those from a series of 4 constant power exercises (CPT) and from a series of 4 RT. Only W' from CPT was higher than from the series of RT and from single RT using VT (p < 0.05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Our previous work showed that the WEP in a standard 3 min all‐out test can be used to estimate the W ′ (Vanhatalo et al 2007); however, it was not shown whether the magnitude of the WEP parameter would be affected by its temporal allocation during the test. It has now been demonstrated that the magnitude of the W ′ remains the same for constant single work rate exercise (Hill, 1993; Smith & Hill, 1993; Hill & Smith, 1994; Morton & Billat, 2004); for stepwise variations of constant work rates (Fukuba et al 2003); for incremental ramp exercise (Morton et al 1997; Pouilly et al 2005); and, assuming that WEP is equivalent to W ′, for combinations of constant work rate and all‐out exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work showed that the WEP in a standard 3 min all‐out test can be used to estimate the W ′ (Vanhatalo et al 2007); however, it was not shown whether the magnitude of the WEP parameter would be affected by its temporal allocation during the test. It has now been demonstrated that the magnitude of the W ′ remains the same for constant single work rate exercise (Hill, 1993; Smith & Hill, 1993; Hill & Smith, 1994; Morton & Billat, 2004); for stepwise variations of constant work rates (Fukuba et al 2003); for incremental ramp exercise (Morton et al 1997; Pouilly et al 2005); and, assuming that WEP is equivalent to W ′, for combinations of constant work rate and all‐out exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The power output associated with PET and CP were between VT 1 and VT 2 . Moritani et al [21] and Pouilly et al [29] have shown that CP is equivalent to VT 1 . On the other hand, Smith and Jones [34] demonstrated that CP corresponds to VT 2 .…”
Section: Discussionmentioning
confidence: 98%
“…These tests are not only time consuming, but also physically and mentally demanding for the athlete. For this reason, previous studies already explored alternative test protocols, including a 3-min all-out test (4), a ramp-sprint test (5) or a simple ramp incremental test (6). Of these, a ramp incremental test seems to be the most feasible alternative as it can be easily tailored to the individual by adjusting the ramp slope and because these tests are already widely used in both sports and clinical practice (7).…”
mentioning
confidence: 99%
“…It should be noted that Black et al (17) calculated W 0 only as the work done above CP and did not investigate its replacement by RCP. Actually, Pouilly et al (6) were the first who attempted to derive CP and W 0 concomitantly from a single ramp incremental test. However, the results of that study may be of little significance as the authors incorrectly used gas exchange threshold (GET) instead of RCP as a surrogate for CP.…”
mentioning
confidence: 99%